Association between spasticity and neuropathic pain in patients with multiple sclerosis - Afanasjeva , B.; Balnytė , R. (Neurologijos seminarai, 2019)
Background. Multiple sclerosis (MS) is a chronic inflammatory autoimmune demyelinating central nervous system disease. Spasticity is one of the disability causing complications in patients with this disease. Spasticity can play a role in the emergence of neuropathic pain which further aggravates the patient’s daily living.Aim. To evaluate the association between spasticity and neuropathic pain in patients with multiple sclerosis.Methods. Patients with MS have been included in the study. The disability of patients with MS was assessed using the Expanded Disability Status Scale (EDSS). Spasticity was evaluated on both sides of the elbow and knee joints, using the modified Ashworth spasticity scale. Neuropathic pain was assessed using the neuropathic pain diagnostic questionnaire (DN4).Results. The study involved 59 patients (39 women, 20 men): with relapsing-remitting MS 52 (88.1%) and with progressive MS 7 (11.9%). The higher degree of disability was estimated in patients with progressive disease form 6.36±1.38, relapsing-remitting disease form 4.38±1.4 (p=0.001). Spasticity localization (N=35): within elbow joint 2 (5.71%), within knee joint 27 (77.14%), within elbows and knee joint 6 (17.15%). Neuropathic pain was detected in 33 patients (55.9%). The localization of neuropathic pain (N=33): in the upper extremities 5 (15.15%), in the lower extremities 23 (69.7%), in both extremities 5 (15.15%). The nature of neuropathic pain: burning 18 (30.5%), resembling of painful coldness 14 (23.7%), resembling of electric current spreading 11 (18.6%). Patients with spasticity more often complained of neuropathic pain (r=0.655, p=0.0001). A higher spasticity may be associated with a higher pain intensity (r=0.536, p=0.0001). The localization of spasticity may be related to the location of the neuropathic pain, because the joint which was assessed with spasticity, the pain was felt in the same joint as well (p=0.0001).Conclusions. The examined patients were diagnosed with MS at the middle age, the majority of subjects had the relapsing-remitting disease, and disability was higher in the patients with progressive forms. Spasticity was reported in more than half of the patients with MS. Spasticity was more common in women than in men. Neuropathic pain was most commonly occurring in the lower extremities, less frequently in the upper extremities. Patients usually experienced burning pain, in some cases sensation of painful freezing and electrical shock. Patients with spasticity had a higher incidence of neuropathic pain. Greater spasticity may be associated with a higher intensity of pain and the localization of spasticity may be associated with a neuropathic pain location.
Keywords: multiple sclerosis; spasticity; neuropathic pain